Utility and validity of the Brief Psychiatric Rating Scale (BPRS) as a transdiagnostic scale. (August 2022) - Hofmann, Andreas B.; Schmid, Hanna M.; Jabat, Mounira; Brackmann, Nathalie; Noboa, Vanessa; Bobes, Julio; Garcia-Portilla, Maria Paz; Seifritz, Erich; Vetter, Stefan; Egger, Stephan T.
Highlights: The Brief Psychiatric Rating Scale is useful for transdiagnostic assessment. Network analyses show close interplay of symptoms and functionality. BPRS and mini-ICF-APP show good internal consistency. Abstract: The Brief Psychiatric Rating Scale (BPRS) was originally conceived to assess psychopathology in several psychiatric disorders, making it an appropriate candidate to be used as a transdiagnostic instrument. We analyzed the utility and validity of the BPRS in a diagnostically heterogeneous sample of 600 psychiatric inpatients. As a comparator, we chose the mini-ICF-APP, a scale used to measure functioning and impairment across the diagnostic spectrum. Both scales had good internal consistency. The BPRS and the mini-ICF-APP showed a moderate correlation, with good levels of agreement. We were able to identify general symptoms present across the diagnostic spectrum, influencing severity and a cluster of symptoms specific for each diagnosis. Our results show the utility and validity of the BPRS as a transdiagnostic assessment tool that could easily be introduced in routine clinical work.